Sol de invierno: aspectos emocionales del paciente renal crónico (2006)
In the present paper is discussed the most important emotional characteristics associated with the form that the patients with chronic renal insufficiency face the hemodialysis treatment. The adaptation process that is considered, important element in the people emotions, involve the patient and their particular ways of defense before the desease like main protagonists, as well as the support of the hospital medical resources, the human team that offers support and the family like important factor to avoid isolation problems whit the patient. With the balance of this adaptation process, as all chronic disease, underlying problems to the patient self-steam are prevented, the corporal image that construct and difficulties centered in his/her daily relations. Key words: adaptation process, chronic renal patient, emotions, nephrology.